2021
DOI: 10.2147/dmso.s264735
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Concentrations in Non-Obese and Obese Non-Diabetes Nigerian-Africans

Abstract: Background Controversial findings exist on the role of leptin in obesity and its correlation with metabolic variables, with few data emanating from Nigerian-Africans. Plasma leptin was therefore determined in obese and non-obese. Its relationship with obesity indices and metabolic variables were further envisaged. Materials and Methods A cross-sectional comparative study on 87 randomly-selected non-diabetes Nigerians distributed into 3 groups (24 normal, 23 pre-obese an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…Our study revealed that there was no difference in concentration of leptin between obese, obese RA and nonobese women. This result disagrees with previous study concluded that leptin hormone showed highly significant differences among obese and non-obese women (28) .…”
Section: Estrogen Hormonecontrasting
confidence: 99%
“…Our study revealed that there was no difference in concentration of leptin between obese, obese RA and nonobese women. This result disagrees with previous study concluded that leptin hormone showed highly significant differences among obese and non-obese women (28) .…”
Section: Estrogen Hormonecontrasting
confidence: 99%